2015
DOI: 10.1007/s11032-015-0291-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving resistance of different apple cultivars using the Rvi6 scab resistance gene in a cisgenic approach based on the Flp/FRT recombinase system

Abstract: Cisgenic apple plants of two different cultivars were developed by transferring the Rvi6 scab resistance gene of Malus floribunda 821, using a new transformation vector based on the Flp/FRT recombinase system. Transformation experiments on seven different cultivars resulted in 22 transgenic lines for the cultivars 'Brookfield Baigent', 'Mitchgla', 'Novajo', and 'Pinova', whereby 16 lines thereof were resistant to Venturia inaequalis strain 104 (race 1).Analysis of the transgenic lines revealed Rvi6 mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…About 3,200 explants were subjected to heat shock activation of the Flp recombinase. The negative D-amino acid / dao1 selection system proposed by Hättasch et al [ 42 ] could not be applied, as it was recently found that the selective medium containing D-Ile hinders the regeneration [ 24 ]. On this account PCR was used to screen the obtained putative cisgenic regenerants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 3,200 explants were subjected to heat shock activation of the Flp recombinase. The negative D-amino acid / dao1 selection system proposed by Hättasch et al [ 42 ] could not be applied, as it was recently found that the selective medium containing D-Ile hinders the regeneration [ 24 ]. On this account PCR was used to screen the obtained putative cisgenic regenerants.…”
Section: Resultsmentioning
confidence: 99%
“…The first cisgenic apple lines with scab resistance were developed by Vanblaere et al [ 23 ]. Würdig et al [ 24 ] and Krens et al [ 25 ] later developed further cisgenic apple lines with Rvi6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Würdig et al. ). Additional effects of the terminator type and length were discussed by the same authors.…”
Section: Cisgenesis/intragenesismentioning
confidence: 98%
“…), while new cisgenic apples with the same trait have been developed using an alternative recombinase system (Würdig et al. ). Furthermore, marker‐free cisgenic potato ( Solanum tuberosum ) plants expressing late blight resistance genes from S. stoloniferum ( Rpi‐sto1 ) and S. venturii ( Rpi‐vnt1.1 ) have been produced by Agrobacterium‐ mediated transformation without using any marker gene but PCR for the selection of transformed plants.…”
Section: Cisgenesis/intragenesismentioning
confidence: 99%